FINANCIAL LEVERAGE AND CORPORATE SURVIVAL: EVIDENCE FROM SELECTED FIRMS IN NIGERIA - Yagana Alhaji Baba; Abdulgaffar Badmus Olayiwola; Falmata Baba Abba (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
The study assesses the impact of financial leverage on corporate survival of companies in cement industry in Nigeria over a period of 3 years (2013-2015). Total Debts to Total Assets Ratio (TDTA) and Total Debts to Total Equity Ratio (TDTE) are proxies for financial leverage while Return on Assets (ROA) and Probability of Bankruptcy (Probankr) proxied corporate survival. In addition, two control variables: Firm size (fmsize) and sales growth were used. The study population was the four (4) listed cement companies on the Nigeria Stock Exchange as at 2006 which also formed the sampled size. The study used panel data from annual reports of these companies and were analyzed using Regression (Ordinary Least Square). The study shows that TDTA and FMSIZE have significant positive relationship with ROA. TDTE and SALESGTH however, show negative insignificant relationship with ROA. On the other, TDTA, TDTE and FMSIZE have insignificant positive relationship with PROBANKR. SALESGTH however, shows a negative insignificant relationship with PROBANKR. It was recommended among others that cement companies in Nigeria should take advantage of trade-off theory of capital structure by using debt to make a better return on equity.